Infrared drying of Clinacanthus nutans leaves - Abdullah, Sriyana; Yusof, Yus Aniza; Rukunudin, Ibni Hajar; Abdul Karim Shah, Nor Nadiah; Abdul Razak, Norawanis (John Wiley and Sons, 2022)
Clinacanthus nutans herbal leaf was dried using an infrared dryer under different power levels (100 W, 200 W, and 300 W) and at different distances between infrared source and samples (10 cm, 20 cm, and 30 cm). Results showed that the drying rate increased when power levels increased and distances decreased. There were found that Midili and Kucuk, Modified Henderson and Pabis, Verma, Two Term, and Wang and Singh gave the best fitting to the experimental moisture ratio for a specific drying treatment. The moisture diffusivity values determined were 4 × 10−11 to 3.09 × 10−10 m2/ s and the activation energy values ranged from 30.81 to 50.58 W/g. Infrared drying can be an option for quick preservation technique for C. nutans herbal leaves as it gave a shorter drying time which could optimize the energy usage. Novelty impact statement: The drying rate of C. nutans leaves was able to increase at a faster rate by infrared radiation as compared to the conventional methods. This result gave a significant reduction of drying time that may reduce energy consumption and enhance the physicochemical properties of the herb.